PENGARUH CREATIVE TOURISM SAUNG ANGKLUNG UDJO TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN (Survei pada Pengambil Keputusan Kelompok Rombongan Sekolah Untuk Berkunjung ke Saung Angklung Udjo) - Bellani, Novika; Siswhara, Gita (Universitas Pendidikan Indonesia, 2012)
Bandung city is one of the cities in West Java has potential tourism that can be relied on, and one of the destination in Saung Angklung Udjo. Saung Angklung Udjo offers a package of art and cultural of West Java that attract tourist. The number of tourist visited in Saung Angklung Udjo continue to rised from 2004 until 2010. The increase in the number of tourist are most significant in 2008. Creative tourism is one of the strategy that can be used to increase visitor and continous visitor. In connection with these research conducted that creative tourism in Saung Angklung Udjo influence tourist visit decision. The purpose of this research is to find creative tourism influenced visiting decisions of Saung Angklung Udjo. Technique of sampling is saturated sampling. The method used in this research is explanatory survey by using ordinal scale. Analyze from this research used Path Analysis with a software computer tools SPSS 19.0. The result of this research found Creative Tourism influenced significantly 37,8% and the rest influence other factors. Based on the result of statictical test were obtained that Creative Spectacles, Creative Spaces, and Creative Tourism has an influence on the decision to visit. It can be conclude that creative spectacles, creative spaces, and creative tourism influence the visiting decision of Saung Angklung Udjo.